The logic of business strategy - Henderson, Bruce D. (Cambridge, Mass. : Ballinger Pub. Co., 1984)
The awareness of natural competition as a systematic effect is century old. For strategy to be possible, it is necessary to be able to imagine and evaluate the possible consequences of alternate courses of action.
Includes index.
Keywords: Business planning